105k views
1 vote
Plz help me with it

Plz help me with it-example-1

2 Answers

4 votes


√(2x + 7) + 1 = √(2x + 14 ) \\ x = 1
User Greg Pavlik
by
5.1k points
6 votes

Answer: a. 1

Explanation:


√(2x+7)+1=√(2x+14)\\\\(√(2x+7)+1)^2=(√(2x+14))^2\\\\2x+7+2√(2x+7)+1=2x+14\\\\2x+8+2√(2x+7)=2x+14\\\\2√(2x+7)=6\\\\√(2x+7)=3\\\\(√(2x+7))^2=(3)^2\\\\2x+7=9\\\\2x=2\\\\x=1\\\\\\Check:\\√(2(1)+7)+1=√(2(1)+14)\\\\\sqrt9+1=\sqrt16\\\\3+1=4\ \checkmark

User Alec Jacobson
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.